Adventures with a Texas humanist - Lee, James Ward, 1931- (TCU Press, 2004)
The author discusses the writers and trends in Texas literature beginning with early twentieth-century writer J. Frank Dobie and Larry McMurtry during the 1960s and places writers, politicians, and cultural leaders in the context of each age.